Circulating Folate, Vitamin B6, and Methionine in Relation to Lung Cancer Risk in the Lung Cancer Cohort Consortium (LC3). (22nd July 2017) - Fanidi, Anouar; Muller, David C.; Yuan, Jian-Min; Stevens, Victoria L.; Weinstein, Stephanie J.; Albanes, Demetrius; Prentice, Ross; Thomsen, Cynthia A.; Pettinger, Mary; Cai, Qiuyin; Blot, William J.; Wu, Jie; et al.
Abstract: Background: Circulating concentrations of B vitamins and factors related to one-carbon metabolism have been found to be strongly inversely associated with lung cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. The extent to which these associations are present in other study populations is unknown. Methods: Within 20 prospective cohorts from the National Cancer Institute Cohort Consortium, a nested case-control study was designed including 5364 incident lung cancer case patients and 5364 control subjects who were individually matched to case patients by age, sex, cohort, and smoking status. Centralized biochemical analyses were performed to measure circulating concentrations of vitamin B6, folate, and methionine, as well as cotinine as an indicator of recent tobacco exposure. The association between these biomarkers and lung cancer risk was evaluated using conditional logistic regression models. Results: Participants with higher circulating concentrations of vitamin B6 and folate had a modestly decreased risk of lung cancer risk overall, the odds ratios when comparing the top and bottom fourths (OR4vs1 ) being 0.88 (95% confidence interval [CI] = 0.78 to 1.00) and 0.86 (95% CI = 0.74 to 0.99), respectively. We found stronger associations among men (vitamin B6: OR4vs1 = 0.74, 95% CI = 0.62 to 0.89; folate: OR4vs1 = 0.75, 95% CI = 0.61 to 0.93) and ever smokers (vitamin B6: OR4vs1 = 0.78, 95% CI = 0.67 to 0.91; folate: OR4vs1 = 0.87, 95% CI = 0.73 to 1.03). We further noted that the association of folate was restricted to Europe/Australia and Asia, whereas no clear association was observed for the United States. Circulating concentrations of methionine were not associated with lung cancer risk overall or in important subgroups. Conclusions: Although confounding by tobacco exposure or reverse causation cannot be ruled out, these study results are compatible with a small decrease in lung cancer risk in ever smokers who avoid low concentrations of circulating folate and vitamin B6.